LEGAL PROTECTION OF CONSUMER PERSONAL DATA PEER TO PEER LENDING THROUGH FINANCIAL TECHNOLOGY IN INDONESIA: AN APPROACHED OF COMPARATIVE STUDY - Putu Eva Ditayani Antari; Ni Gusti Agung Ayu Mas Triwulandari (Jurnal Komunikasi Hukum, 2024)
The development of Fintech cannot be ignored and needs to be managed so that it can provide maximum benefits for the benefit of society. Because in practice there are parties who are harmed, there are more and more cases of protection of consumer personal data, it is interesting to study further about legal protection of consumer data security in the Fintech business in Indonesia, especially in this study, namely Fintech Peer for Peer Lending. Currently cases of misuse of personal data in Indonesia are still high. Efforts to address legal protection issues for Fintech consumer personal data are contained in POJK Number: 1/Pojk.07/2013 concerning Consumer Protection in the Financial Services Sector and regarding what data must be protected has also been regulated in SOJK Number 14/Seojk.07/2014 concerning Confidentiality and Security of Data and/or Consumer Personal Information, and SOJK Number 18/Seojk.02/2017 Concerning Information Technology Governance and Risk Management in Information Technology-Based Borrowing Services. The existence of these regulations is still not able to resolve personal data issues, so the government makes Law Number 27 of 2022 Concerning Personal Data Protection. The problem approach method used in this research is normative juridical. The source of legal materials in this study uses secondary materials as the main materials. The method of collecting legal materials by means of library research, was analyzed using a qualitative approach to secondary legal materials. The author's recommendations for further research related to the personal data supervisory agency which is currently still in the process of being formed, the author suggests studies related to the authority and role of the personal data monitoring agency in Indonesia.